PHENOMENOLOGY STUDY OF DIRECT VILLAGE CASH ASSISTANCE (BLTDD) FOR POOR COMMUNITIES AFFECTED BY COVID-19 IN INDRAGIRI HULU DISTRICT - Airine Yulianda; Kurnia Dewi (LPPM Press STIE Indragiri Rengat, 2022)
The purpose of this study was to analyze the effectiveness of providing direct village cash assistance (BLT-DD) covid-19 using measurement indicators in the form of timeliness and accuracy of choice, as well as to analyze the impact caused by the provision of direct village cash assistance (BLT-DD) covid. -19 from an economic and social perspective for the people of Indragiri Hulu Regency. This study uses a descriptive method with a qualitative approach. The results of this study indicate that the data collection process to the distribution of BLT-DD in Indragiri Hulu Regency has been effective in terms of timeliness and accuracy of choice. In addition, the Covid-19 BLT-DD can help the community's economy in the midst of a pandemic